SISTEM PENGAJUAN ASSESSMENT KEBENCANAAN BERBASIS WEBSITE UNTUK MENINGKATKAN RESPONS TANGGAP DARURAT DI KABUPATEN KEBUMEN - Khafidurohman, Khafidurohman; Fadjeri, Akhmad (P3M Politeknik Negeri Indramayu, 2025)
Kebumen Regency, located on the southern coast of Java, faces a high disaster risk due to its position in a tectonic subduction zone that can trigger major earthquakes. The presence of the Sempor and Wadaslintang dams further increases vulnerability to potential failures during seismic events. This study identifies the need for a rapid and accurate disaster assessment system to strengthen preparedness and emergency response. To address this, we developed a web-based system that enables both communities and government officials to collect real-time data from affected areas. System development, functionality testing, and performance evaluation were conducted to assess its effectiveness. The results show that the system delivers timely and accurate data, enhances coordination, and improves community resilience. This system is expected to be an efficient solution for disaster management in Kebumen Regency.